Diagnosis and treatment of solid pseudopapillary neoplasm of the pancreas in children: A report of 18 cases - Maimaijiang, Ayiguzaili; Wang, Haiyun; Li, Wanfu; Wang, Yaqi (Frontiers in Pediatrics, 2022)
Purpose:To investigate the effect of MYCN on the proliferation, invasion and migration of neuroblastoma cells and its molecular mechanism. Methods: The clinical data of 18 children with solid pseudopapillary tumor of pancreas treated in our hospital from January 2012 to June 2021 were analyzed retrospectively. The age range was 8 to 16 years old, the average age was 11.67 years old, the median age was 11.5 years old, including 3 boys with an average age of 10 years old and 15 girls with an average age of 12 years old. 2 cases were admitted to hospital because of trauma, 7 cases were found in physical examination, and 9 cases were admitted with abdominal pain as the main complaint. Enhanced CT examination was performed before operation, nuclear magnetic resonance examination and abdominal ultrasound examination were performed in some children, and plain CT scan was performed after operation. Results: Solid pseudopapillary tumor of pancreas in children is a rare low-grade malignant solid tumor with no specific clinical manifestation and laboratory examination. Preoperative diagnosis mainly depends on enhanced CT. Surgical resection of tumor is a reliable treatment, and the specific operation is mainly determined by the location, size and invasion of surrounding tissue. At present, there is no evidence of the effectiveness of other treatment options, and surgical resection of tumor has a good prognosis. Conclusion:Our work demonstrated the carcinogenic activity of miR-20a-5p in promoting the proliferation,invasion and migration of NB cells via the MYCN/miR-20a-5p /NFKBIB/NF-κB signaling axis.